Using Board Game Through TTW Strategy in Descriptive Writing - Muntiari, Nur Sholikha; Megawati, Fika (IJET (Indonesian Journal of English Teaching), 2021)
This research aims to find out the effect of using board game through TTW strategy on seventh grade students’ writing skill in descriptive text. Quasi-experimental design was implemented to the seventh grade in one of junior high school. The subject of this study was the whole population of seventh grade students in junor high school, in total 81 students. The data collection was taken from pre-test and post-test. The average score of experimental group is 73.81, and the average score of control group is 57.46. Moreover, the hypothesis test shows that Ho is rejected because tcounting (5.71) is higher than ttable (2.31). In TTW strategy the students collaborate between three activities those are Think, Talk, and Write. TTW strategy is more effective becausethe students have enough time in learning process in a class. Additionally, the result of this study indicates that using board game through TTW strategy gives significant effect for developing English writing skill.